The circle of the wickedness: The ragazzi by Pasolini, and "Malagueta, Perus e Bacanaço" by João Antônio - Polinesio, Julia Marchetti (Revista de Italianística, 1993)
The article analyzes the similarities in The Ragazzi, by Pasolini, and "Malagueta, Perus e Bacanço", by Joâo Antônio. Both have as theme the representation of characters from low life of big cities, as Rome and São Paulo. Besides the sameness of the theme - the lack (of residense, money, love and security)-, the article points out other of approximation: the narrative focus; the language full of slang or dialect; the recurrent themes in the underworld ambience, such as the death, the frigth, the cruelty.